Public bureaucracy and climate change adaptation - Biesbroek, Robbert; Peters, B. Guy; Tosun, Jale (Review of policy research, 2018)
Despite recognizing the importance of public bureaucracies in governing climate change, our knowledge of how their behavioral and structural characteristics influence climate change adaptation policy is limited. This article provides an introduction to a collection of studies that seeks to explore the link between climate change adaptation and public bureaucracies, and to distill lessons for the scholarship on adaptation as well as the persistent debates on the role of administrative traditions in public policy. The articles in the special issue demonstrate that how state and social actors are organized, the ways in which scientific advice enters bureaucracies, and uniformity in the making and implementing of policy matter for adaptation policy. We conclude that the concept of administrative traditions is still necessary for understanding the choices made by public actors, but contend that other factors such as economic motives and political willingness should be considered more critically in the literature on administrative traditions.